Age-dependent changes in plasma concentrations of 25-hydroxyvitamin D may complicate vitamin D status assessment of immature cats - Backus, Robert C.; Ueda, Devon C. (Frontiers in Veterinary Science, 2024)
Background Vitamin D deficiency and excess in clinically presented cats conventionally is diagnosed by comparison of patient plasma 25-hydroxyvitamin D (25(OH)D) concentration with plasma reference intervals determined in healthy adult cats. For immature cats, validity of this vitamin D status assessment method is uncertain.Objective The overall objective was determination of whether plasma concentration of 25(OH)D and other vitamin D metabolites in immature cats markedly change with developmental age as has been reported in other species.Methods Four male and 4 female domestic short-hair kittens from weaning were continuously presented a single nutritionally adequate growth-diet. Concentrations of 25(OH)D and 24,25dihydroxyvitamin D (24,25(OH)2D), and calcitriol were quantified in plasma of jugular venous blood collected at 12, 15, 18, and 21 weeks and 1 year of age. Plasma was liquid and solid-phase extracted and fractionation by normal-phase HPLC, and 25(OH)D and 24,25(OH)2D quantified by reversephase HPLC-UV and calcitriol by RIA.Results Plasma epi-3-25(OH)D and 25(OH)D concentrations increased (P < 0.001) with age so that by study end the concentrations rose by 1-and 2-fold, respectively. Concentrations of epi-3-25(OH)D relative to 25(OH)D were 30% at 12 weeks and 20% at 1 year. Between ages 12 and 21 weeks, rises in 25(OH)D concentration were positively correlated with body weight gains (ρ = 0.952, P < 0.001) and 24,25(OH)2D concentrations were consistently greater than 25(OH)D concentrations (P < 0.001). At 1 year of age, concentrations of 24,25(OH)2D declined below those of 25(OH)D and epi-3-24,25(OH)2D consistency occurred in low concentrations. Vitamin D2 metabolites and sex differences in metabolite concentrations were not observed.Conclusions Reliance on quantification of plasma 25(OH)D concentration for vitamin D status assessment in kittens may be confounded by developmental changes in 25(OH)D independent of vitamin D intake. High 24,25(OH)2D concentration and occurrence of epi-3-25(OH)D in plasma additionally may interfere with the quantification.